Analysis of the Right Over Roof Slab from the perspective of the incapacities system / Análise do Direito Real de Laje sob a ótica das incapacidades - Divino, Sthéfano Bruno Santos; Magalhães, Rodrigo Almeida (Revista de Direito da Cidade, 2020)
Abstract On the one hand, the Civil Code, in its art. 1.748, IV, authorizes the sale of properties in cases where it is judicially authorized. On the other hand, art. 1.749, I, of this same legal provision, establishes the prohibition of the guardian to acquire for himself or by interposed person, by private contract, such property belonging to the minor. Among these, the problematic of this article: can the curator/tutor establish and acquire the Right over Roof Slab of his curated/tuteled? For its due satisfaction, the first topic concerns the contextualization and approach of the right over slab in the contemporary legal-legislative-social scenario, as well as its peculiarities and legal requirements for its characterization. Subsequently, the general rules of guardianship and custody are discussed with regard to the (im) possibility of sale of assets of the incapable subjects. In the end, it is possible for the guardian to establish and acquire the Right Over Roof Slab of the tuteled/curated before the characterization of the legal prohibitions imposed, since the property remains in the tuteled/curated property and such conduct does not seem to bring no patrimonial or existential damage to these subjects. However, some requirements are stipulated. The construction of the present reasoning is anchored in the dogmatic, hermeneutic-concretizing, deductive and integrated research methods. Keywords: Right Over Roof Slab; Civil Law; Trusteeship; Tutorship; Roof Slab. Resumo: De um lado, o Código Civil, em seu art. 1.748, IV, autoriza a venda de imóveis nos casos em que for autorizado judicialmente. De outro, o art. 1.749, I, deste mesmo dispositivo legal, estabelece a vedação de o tutor adquirir para si, ou por interposta pessoa, mediante contrato particular, tais bens pertencentes ao menor. Entre estes, a problemática do presente artigo: pode o curador/tutor estabelecer e adquirir Direito de Laje de seu curatelado/tutelado? Para sua devida satisfação, o primeiro tópico se incumbe da contextualização e abordagem do direito de laje no contemporâneo cenário jurídico-legislativo-social, bem como suas peculiaridades e exigências legais para sua caracterização. Posteriormente, abordam-se as regras gerais da tutela e da curatela com relação à (im)possibilidade de venda de bens dos sujeitos incapazes. Ao final, conclui-se pela possibilidade de o tutor/curador estabelecer e adquirir Direito de Laje do tutelado/curatelado ante a não caracterização das vedações legais impostas, vez que o imóvel ainda permanece em propriedade do tutelado/curatelado e tal conduta parece não trazer nenhum dano patrimonial ou existencial a esses últimos sujeitos. Contudo, estipula-se alguns requisitos. Ancora-se a construção do presente raciocínio nos métodos dogmático, hermenêutico-concretizador, dedutivo e de pesquisa integrada. Palavras-chave: Direito Real de Laje; Direito Civil; Curatela; Tutela; Laje.